2020
DOI: 10.3390/su12062181
|View full text |Cite
|
Sign up to set email alerts
|

Finnish Students’ Knowledge of Climate Change Mitigation and Its Connection to Hope

Abstract: Climate change is a global concern, and the need to address it is urgent. Therefore, climate change education has been developed in recent years. Meaning making, coping strategies, and solution-oriented climate education tasks enable and maintain hope for positive results with regard to climate change. However, there is still uncertainty as to how students’ knowledge of climate change mitigation measures affects their attitudes. In the present study, elementary and secondary students in Finland (n = 950) respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 42 publications
2
22
0
4
Order By: Relevance
“…This is especially true in Canada, where 88% of respondents express concern regarding climate change in the Arctic 1 . Some of the research conducted in Finland indicate that gender, knowledge about climate warming and constructive hope become predictors of attitude towards climate change (Ratinen and Uusiautti, 2020).…”
Section: Changing Environment Of Polar Regionsmentioning
confidence: 99%
“…This is especially true in Canada, where 88% of respondents express concern regarding climate change in the Arctic 1 . Some of the research conducted in Finland indicate that gender, knowledge about climate warming and constructive hope become predictors of attitude towards climate change (Ratinen and Uusiautti, 2020).…”
Section: Changing Environment Of Polar Regionsmentioning
confidence: 99%
“…Finnish female students performed significantly better in topic knowledge of biology and chemistry. Ratinen and Uusinautti [66] found that knowledge of climate change among the Finnish female elementary and high-school students predicted climate change mitigation. Finnish female students were also shown to be more likely than their male counterparts to choose science as a future career.…”
Section: Discussionmentioning
confidence: 99%
“…Kasvihuoneilmiö mielletään usein virheellisesti ainoastaan ympäristöongelmaksi, ja esimerkiksi otsonikadon, ilmansaasteiden ja roskaamisen rooliin liittyy monia väärinymmärryksiä (Ratinen & Vettenranta, 2018). On myös osoitettu, kuinka tiedot ilmastonmuutoksen hillinnän keinoista ovat puutteellisia sekä oppilailla (Ratinen & Uusiautti, 2020) että opettajiksi opiskelevilla (Tolppanen, Claudelin & Kang, 2020). Ratinen (2016) onkin korostanut, että ilmastonmuutoksen ymmärtäminen vaatii riittävää ymmärrystä ilmiöön vaikuttavista luonnontieteellisistä prosesseista.…”
Section: Johdantounclassified